2020
DOI: 10.1007/s11136-020-02576-5
|View full text |Cite
|
Sign up to set email alerts
|

Filling the psycho-social gap in the EQ-5D: the empirical support for four bolt-on dimensions

Abstract: Purpose The EQ-5D is the most widely applied generic preference-based measure (GPBM) of health-related quality of life (HRQoL). Much concern has been raised that its descriptive system is lacking psycho-social dimensions. A recent paper in this journal provided theoretical support for four dimensions to fill this gap. The current paper aims to provide empirical support for these suggested bolt-on dimensions to the EQ-5D. Methods We use data from the comprehensive Multi-Instrument-Comparison (MIC) study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 28 articles that were included, 3 articles were studies that identified possible bolt-ons (category A "identification or development of possible suitable bolt-ons"), [23][24][25] 13 articles were psychometric performance studies (category B "psychometric performance studies"), 8,26-37 and 6 articles were valuation studies of EQ-5D 1 bolt-on (category C "health state valuation studies"). 19,20,[38][39][40][41][42] Furthermore, 3 articles were categorized as both categories A and B, [43][44][45] and 3 articles as both categories A and C. 13,21,38 Study populations consisted of a healthy population (n = 17 articles: general public, 13,[19][20][21]24,25,27,30,36,38,[40][41][42][43] random households, 44,45 faculty members 39 ) and patients (n = 11 articles: individuals with a chronic condition, 23 visitors of an outpatient eye clinic, 26 cognitive impaired elderly patients, 18 patients with diabetes, 28 general injury patients, 29,31,35 patients listed for cataract surgery, 32,34 stroke patients, …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Based on the self-developed checklist for bolt-on studies, 3 studies in category A1 ("studies that identified possible suitable bolt-ons") scored doubtful, 23,24,44 and 3 studies adequate, 25,43,45 whereas for category A2 ("studies that developed possible suitable bolt-ons") 1 study was inadequate 40 and 2 studies were very good. 21,38 For category B, 3 studies scored inadequate, 26,34,36 6 studies doubtful, 18,27,28,30,32,33 and 4 studies adequate. 29,31,35,37 Furthermore, 1 study in category C was judged inadequate, 19 3 studies doubtful, 21,38,39 1 study adequate, 41 and 4 studies very good.…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations